Liquid-liquid equilibria for methanol-methyl oleate-water-oleic acid system - Dexter, Zick Donny (2010)
Biodiesel is one of the best substitutes for petroleum-based fuels, mainly because of its renewability and biodegradability. Biodiesel can be produced via esterification between alcohols and fatty acid. This process usually requires distillation to purify the biodiesel. Therefore, it requires thermodynamic properties such as equilibrium data of the related components. Knowledge of the phase equilibrium conditions of the reactive mixture is essential to explore possible operating conditions for the reactor and the downstream separation process. In this study, liquid-liquid equilibrium (LLE) data were measured for the quaternary system of Methyl Oleate-Water-Oleic Acid-Methanol at (40 and 50)oC and at atmospheric pressure. A UNIFAC activity coefficient model was used to predict the properties of the coexisting phases at equilibrium. Three ternary systems were developed which are Methanol-Oleic Acid-Water, Oleic Acid-Methyl Oleate-Water, and Methanol-Methyl Oleate-Water. These three systems later were combined together and became a quaternary system. Each of the components was mixed together in a cell and two separated liquid phases were obtained after four hours of mixing and five hours of settling. Both layers will be analyzed using Gas Chromatography with Flame Ionization Detector (GC-FID) and data was obtained. For this quaternary system, the predictions of UNIFAC can be slightly deviate with the experimental result. The temperature also showed to have an effect in the solubility when increasing the temperature.